A profile’s design for parallel applications modelling - Giulianelli, Daniel Alberto; Pons, Claudia Fabiana; Rodríguez, Rocío Andrea; Vera, Pablo Martín; Fernandez, Victor Manuel (Revista Colombiana de Computación, 2010)
During the last times hardware progress has reached home computers with technologies that were only used in main frames. Clear examples of this statement are multiple core personal computers. As this new hardware becomes popular it is neccessary to change the way of designing applications in order to be able to use it. UML is a wide general-purpouse modeling language that counts with a graphic vocabulary. In some cases, when a particular application is going to be modeled, the UML’s graphic vocabulary, results too abstract. That’s why a specialization of the language is neccessary by means of the adding of new artifacts that allows modeling the special characteristics of the particular domain. This paper shows a profile that specializes UML to facilitate the parellized applications modeling, considering their own characteristics.